Molecular Dynamics Simulations Elucidate the Mechanism of Proton Transport in the Glutamate Transporter EAAT3 - Heinzelmann, Germano (The Biophysical Society, 2014)
The uptake of glutamate in nerve synapses is carried out by the excitatory amino acid transporters (EAATs), involving the cotransport of a proton and three Na(+) ions and the countertransport of a K(+) ion. In this study, we use an EAAT3 homology model to calculate the pK(a) of several titratable residues around the glutamate binding site to locate the proton carrier site involved in the translocation of the substrate. After identifying E374 as the main candidate for carrying the proton, we calculate the protonation state of this residue in different conformations of EAAT3 and with different ligands bound. We find that E374 is protonated in the fully bound state, but removing the Na2 ion and the substrate reduces the pK(a) of this residue and favors the release of the proton to solution. Removing the remaining Na(+) ions again favors the protonation of E374 in both the outward- and inward-facing states, hence the proton is not released in the empty transporter. By calculating the pK(a) of E374 with a K(+) ion bound in three possible sites, we show that binding of the K(+) ion is necessary for the release of the proton in the inward-facing state. This suggests a mechanism in which a K(+) ion replaces one of the ligands bound to the transporter, which may explain the faster transport rates of the EAATs compared to its archaeal homologs.